"I can think, I can wait, I can fast": Teaching food literature and experiential learning. (April 2017) - Anantharam, Anita
The idea of self-sufficiency resonates with feminist activists because the political thrust of the various movements for women's rights—beginning with Mary Wollstonecraft's plea for women's access to education in her famous Vindication —hinged on finding sustainable solutions to the stranglehold that social, political, and economic institutions have on women's lives. If the pivotal movement of feminism, in other words, is about increasing women's sovereignty in a patriarchal world, the emerging "local/global" food movements provide a dynamic opportunity to understand how the personal can be refashioned into political action. The point of this essay is thus twofold: first, to show that food literature is an excellent medium to teach transnational feminist theories and practices; and second, to offer some of our strategies for feminist civic engagement through reclaiming the idea of "the personal is political."